Eva 85. - Limerick City Gallery of Art; Exhibition of Visual + Art Limerick 1985 (Limerick : Limerick City Gallery, 1985)
Baker, Bob ; Barrett, Marie ; Boydell, Cormac ; Coleman, James ; Coleman, Michael ; Collins, Niamh ; Commerford, Helen ; Cooper, Frank Lee ; Cronin, Ann ; Delmage, Mary ; Dennis, Jill ; Donnelly, Micky ; Egan, Felim ; Fearon, James E. ; etc.
Eva 85, Limerick City Gallery, Limerick, 19 October - 23 November 1985
boek